Hydrogen Generation: Plasmonic ZnO/Ag Embedded Structures as Collecting Layers for Photogenerating Electrons in Solar Hydrogen Generation Photoelectrodes (Small 17/2013). Issue 17 (3rd September 2013) - Chen, Hao Ming; Chen, Chih Kai; Tseng, Ming Lun; Wu, Pin Chieh; Chang, Chia Min; Cheng, Liang‐Chien; Huang, Hsin Wei; Chan, Ting Shan; Huang, Ding‐Wei; Liu, Ru‐Shi; Tsai, Din Ping
<x xml:space="preserve">Abstract</x> A new fs‐laser fabrication technique is applied to generate patternable plasmonic nanostructures, in which both localized surface plasmon resonance in metal nanoparticles and plasmon polaritons propagating at the metal/semiconductor interface are available for improving the capture of sunlight and collecting of charge carriers. As reported by R. S. Liu, D. P. Tsai, and co‐workers on page 2926, plasmoninduced effects simultaneously enhance the photoresponse, by both improving optical absorbance and facilitating the separation of charge carriers. This strategy can be used to improve the effectiveness of embedded plasmonic nanostructures in hydrogen generation. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>